Self‐Healing, High Adherent, and Antioxidative LbL Multilayered Film for Enhanced Cell Adhesion. Issue 11 (3rd March 2020) - Yuan, Renqiang; Luo, Chenxi; Yang, Yifan; He, Chunpeng; Lu, Zuhong; Ge, Liqin
Abstract: Cell adhesion acts as a complex process that is hardly promoted through surfaces with a single performance. Controlling the cell's adhesion on the interfaces between the synthetic materials and the biological environments remains a real challenge in the biomedical fields. Herein, based on RGD peptide modified carboxymethyl chitosan (CCS‐R) and dopamine modified oxidized alginate (OALG‐D), a layer‐by‐layer (LbL) self‐assemble multilayered (CCS‐R/OALG‐D)15 film is developed. The multifunctional (CCS‐R/OALG‐D)15 film with a self‐healing, highly adherent, biocompatible, and antioxidative biomatrix property for the cell adhesion is fabricated with the Schiff‐base bond, electrovalent bond, and hydrogen bond. The LbL multilayered film exhibits the significant cell adhesion ability for the normal human dermal fibroblast cells and the coral Acropopa formosa cells. Furthermore, it holds high self‐healing efficiency (88.8%), excellent adhesion strength (adhesive stress: 61.1 MPa), and outstanding antioxidation (free radical scavenging rate: 86.8%). Furthermore, it is demonstrated that the LbL multifunctional film, as a culture matrix, has prolonged the survival of the coral Acropopa formosa . Therefore, the incorporation of a self‐healing, high adhesion, superior cell adhesion, and antioxidation property into a single LbL self‐assembly film provides a promising platform for regenerative medicine. Abstract : The layer‐by‐layer self‐assembly (CCS‐R/OALG‐D)15 film containing the Schiff base bond, electrovalent bond, and hydrogen bond is developed for enhanced adhesion of cells (normal human dermal fibroblasts and coral Acropopa formosa cells). It holds high self‐healing efficiency (≈88%), excellent adhesion strength (≈61 MPa), and outstanding antioxidation (≈86%). The survival of coral explants gets promoted on it, promising for regenerative medicine.